Potensi Bumdes Berbasis Syariah Pasca Legalisasi UU Nomor 11 Tahun 2020 Tentang Cipta Kerja - Nunik Nurhayati; Brillian Feza Eryan Prasetya; Rina Nur Widyastuti; Muhammad Edi Hermawan (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to discuss the regulation of Village Own Enterprise (BUMDes) and the opportunities for sharia BUMDes after the legality of the Job Creation Act. The research method used is normative-juridical research, which is carried out by analyzing interrelated laws and regulations, as well as collecting related information through books, scientific journals, scientific research results, articles, and other valid supporting sources from the internet. Then based on these sources will be processed and analyzed based on the formulation of the problem that has been determined, in order to obtain a solution to the problems that occur. The emergence of the formulation of BUMDes in the Village Act has become an essential provision for villages to be able to try to advance their territory. Villages with all the local culture inherent in them are required to be able to advance independently, with the spirit of mutual cooperation through the implementation of BUMDes in their area. After the issuance of the Job Creation Act, BUMDes underwent significant changes that required a legal entity as its embodiment. However, to date, there have been no further provisions that stipulate with certainty the types of business with legal entities that are relevant to be applied by village communities. In order to reach benefit from the diversity of potentials in the village, the development of sharia cooperative business is a universal recommendation for villages to advance the economy in their area.